Risk factors for lumbar disc herniation in adolescents and young adults: A case–control study - Qi, Le; Luo, Lijuan; Meng, Xianrong; Zhang, Jun; Yu, Tong; Nie, Xinyu; Liu, Qinyi (Frontiers in Surgery, 2023)
Background: While evidence suggests that lumbar disc herniation (LDH) is occurring more frequently in younger people, there is a limited understanding of the risk factors for LDH in this population. The purpose of this study is to comprehensively analyze the risk factors of adolescents and young adults suffering from LDH. Methods: We retrospectively reviewed medical records of all patients with inclusion criteria of being younger than 25 years. We used magnetic resonance imaging (MRI) to confirm LDH from September 2016 to September 2021. In addition, we also collected 104 healthy people in the same age range as the control group from physical examination centera . For all the enrolled people, we investigated gender, BMI, smoking, drinking, genetic history, sitting posture, daily sitting time, traumatic history of lower back, scoliosis and daily exercise time. These factors were statistically analyzed to find out the high-risk factors. Results: A total of 208 young individuals were enrolled to the present study. The mean age of the study group and the control group were 21.06 ± 3.27 years (range 11-25 years) and 21.26 ± 2.23 years (range 15-25 years), respectively. The result of Chi-squared testing showed that there was a significant difference on BMI more than 30 (p  0.001), genetic history (p = 0.004), sitting posture (p  0.001), daily sitting time (p  0.001) and the history of low back trauma (p = 0.002). Besides, multivariate logistic regression also showed that these were high-risk factors related to LDH, especially the duration of daily sitting more than 6h. Conclusions: BMI more than, genetic history, sitting posture, daily sitting time more than 6h and the history of low back trauma are the high-risk factors of adolescents and young adults suffered from LDH. Therefore, proper guidance and education for them, especially the protection of the lower back and the reduction of spinal load, could play a key role in working to prevention and reduce LDH.